Unveiling the potential of Lactobacillus johnsonii in digestive diseases: a comprehensive review - Zhou, Jinjie; Ma, Shuang; Huang, Zhuo; Yao, Qinyan; Yu, Zihan; Chen, Jihua; Yao, Liuqing; Zhu, Lanping; Chen, Xin (Frontiers in Microbiology, 2025)
BackgroundLactobacillus johnsonii (L. johnsonii) is a lactic acid-producing probiotic, possessing the potential to modulate intestinal microbiota balance, which can enhance immune function, and reduce the risk of intestinal infections. In recent years, increasing studies have demonstrated the positive impact of this strain and its metabolites on the health of multiple systems, including the stomach, intestine, liver, and brain.ObjectiveThis article aims to systematically review the mechanisms of action and clinical application progress of L. johnsonii in the prevention and treatment of digestive system-related diseases. The focus is on exploring its systemic regulatory role through the “microbiota-gut-organ axis.”MethodologyBy collating and analyzing recent research findings on L. johnsonii, we evaluated its specific mechanisms in regulating intestinal barrier function, immune response, and neuroendocrine signaling pathways. This strain can be isolated and identified through experimental means, and its population abundance can be quantitatively analyzed, providing a basis for studying its biological functions.ResultsStudies have revealed that L. johnsonii exhibits significant interventional potential in various cross-system diseases, including inflammatory bowel disease (IBD), intestinal infections, Helicobacter pylori (H. pylori)-associated gastritis, non-alcoholic fatty liver disease, and neurodegenerative diseases. These findings further validate the important role of this strain in maintaining intestinal microbiota homeostasis, regulating body metabolism, and brain-gut axis function.ConclusionIn summary, L. johnsonii shows great promise in digestive health by modulating immunity, enhancing the gut barrier and balancing gut microbiota. Future research should further explore its mechanisms of action, aiming to provide a solid theoretical foundation and experimental support for its precise therapeutic reality.